Design of traveling wave slotted waveguide array antenna with high efficiency - Najat Shyaa Jasim Mohammed; Manal Hadi Jaber (Institute of Advanced Engineering and Science, 2023)
The slotted waveguide antenna is one of the most important antennas used in high-frequency applications, in radars, navigation systems, remote sensing systems and communications because of its efficiency and high gains. In this paper, the slotted waveguide antenna was designed and simulated with suitable specifications with a working frequency range of 2-2.45 where this antenna was checked by plotting S parameters in the designed frequency band and we got a very good reflection coefficient for the designed antenna (S11) at the operating frequency, draw and illustrate the three-dimensional radiation pattern of the designed antenna that shows the gain and bandwidth at the operating frequency. The performance of a 9-element slotted waveguide array antenna with an operating frequency of up to 12 GHz was also investigated by plotting the S11 parameters and illustrating the designed antenna directivity diagram.We obtained the reflection coefficient of the designed array antenna (S11) below -23 dB at the operating frequency, and the SWG antenna directivity pattern with a maximum value of=13.2 dB and a minimum value of=-23 dB.